The Effect of Complementary Therapy from Plant Extracts on Breast Milk Production - Lili Farlikhatun; Fitri Ummu Rosyidah; Novia Karmilasari; Seftaliana; Masfupah; Sri Gustina; Rukmini (Jurnal Penelitian Pendidikan IPA, 2024)
Breastfeeding issues arise when mothers cannot produce enough milk to meet their babies' nutritional needs. This study aims to assess the effect of complementary therapies, such as consuming moringa leaves, katuk leaves, soy milk, spinach, young papaya, and using lavender aromatherapy, on increasing breast milk production. The quasi-experimental study involved postpartum mothers on day 4, using a pre-test and post-test design with six variables. Results showed that 83.9% of 56 mothers who consumed moringa leaves, 84.5% of 58 mothers who drank soy milk, 81.3% of 48 mothers who ate katuk leaves, 86.4% of 44 mothers who consumed spinach, 82.7% of 52 mothers who ate young papaya, and 83.3% of 30 mothers who used lavender aromatherapy experienced sufficient breast milk production. These findings demonstrate that all six therapies positively influence breast milk production. It is recommended that healthcare providers routinely offer these complementary therapies to postpartum mothers to support exclusive breastfeeding for their babies.